Your Undergraduate Dissertation : the essential guide for success - Walliman, Nicholas (Sage study skills., 2014)
This guide to all the essential facets of dissertation writing at undergraduate level provides advice for preparing a project and choosing a topic, and guidelines for writing a project proposal and producing a literature review.